2017
DOI: 10.1097/md.0000000000008643
|View full text |Cite
|
Sign up to set email alerts
|

Mercury poisoning through intravenous administration

Abstract: Rationale:Metallic mercury poisoning through intravenous injection is rare, especially for a homicide attempt. Diagnosis and treatment of the disease are challenging.Patient concerns:A 34-year-old male presented with pyrexia, chill, fatigue, body aches, and pain of the dorsal aspect of right foot. Another case is that of a 29-year-old male who committed suicide by injecting himself metallic mercury 15 g intravenously and presented with dizzy, dyspnea, fatigue, sweatiness, and waist soreness.Diagnosis:The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The U.S. Federal Biological Exposure Index of mercury was 50 μg/L in urine ( Kamensky et al, 2019 ). A clinical case reported patients with urinary mercury concentrations of 4,828 μg/L or 458 nmol/L were diagnosed with poisoning ( Lu Q. Y. et al, 2017 ). No related toxicity occurred in 30 days realgar treated rats, and the urinary arsenic concentrations were 10.30 and 3.48 μg/ml at 1–12 and 12–24 h, respectively ( Yi et al, 2019 ; Yi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The U.S. Federal Biological Exposure Index of mercury was 50 μg/L in urine ( Kamensky et al, 2019 ). A clinical case reported patients with urinary mercury concentrations of 4,828 μg/L or 458 nmol/L were diagnosed with poisoning ( Lu Q. Y. et al, 2017 ). No related toxicity occurred in 30 days realgar treated rats, and the urinary arsenic concentrations were 10.30 and 3.48 μg/ml at 1–12 and 12–24 h, respectively ( Yi et al, 2019 ; Yi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mercury intoxications are especially known from the public health disasters in Minamata and Iraq [ 5 , 6 ]. There are just a few reports regarding homicides or suicides by mercury compounds [ 12 14 ]. The common factor in most cases is that victims or perpetrators of mercury intoxications had access to mercury compounds due to their profession [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, suicides as well as homicides with mercury compounds are rare [12][13][14][15]. Nevertheless, there are several reports of homicidal, suicidal and accidental mercury intoxications in the last centuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, once in humans, this element affects different target organs, including the nervous system, kidneys, and liver, causing mental disorders and damage to the motor, reproductive, speech, vision, and hearing systems. Various studies have reported severe cases of poisoning and death due to contamination with this metal [75,76]. When ingested by pregnant women, MeHg has the ability to cross the placental barrier, accumulating in the brain and central nervous system of the developing fetus [77].…”
Section: Environmental and Human Health Impactsmentioning
confidence: 99%